Dermatofibrosarcoma Protuberans with Fibrosarcomatous Change: A Case Report of Rare Entity - Theerawattanawit, Chinathip; Wongjirattikarn, Rachot; Wititsuwannakul, Jade (Thai Journal of Dermatology, 2024)
Dermatofibrosarcoma protuberans (DFSP) is a rare malignancy affecting the skin and underlying soft tissues. Typically characterized by a favorable prognosis with low metastatic and recurrence rates, DFSP can manifest as a subtype with an unfavorable outcome known as DFSP with fibrosarcomatous changes (DFSP-FS). Histologic examination reveals DFSP-FS to exhibit more atypical cellular features and increased mitotic activity compared to the classic DFSP variant. In this report, we detail the case of a 48-year-old Thai female patient presenting with a progressively enlarging mass on the lumbosacral area. Pathological and immunohistochemical analyses confirmed the diagnosis of DFSP-FS. This case presents the rarity of DFSP-FS and emphasizes its distinctive pathological and immunohistochemical characteristics.